Pengaruh Bauran Pemasaran terhadap Kepuasan dan Loyalitas Konsumen Produk Wisata Kuliner di Kota Banda Aceh - Mahrizal Mahrizal; Maisur Maisur (Jurnal Ilmiah Ekonomi Global Masa Kini)
This research focuses on the effect of marketing mix on customer satisfaction and customer loyalty in the city Banda Aceh. The sample used in this study were 150culinary customers in the city of Banda Aceh. The data analysis technique used in this research is quantitative analysis using SEM (Structural Equation Modeling) or models structural equation modeling with program AMOS 4. The results showed that the marketing mix of product, price, location and service variables had an effect on customer loyalty, only location and service have an effect on customer loyalty for purchasing culinary products in the city of Banda Aceh.